Plasma Biomarkers Differentiate Parkinson’s Disease From Atypical Parkinsonism Syndromes - Lin, Chin-Hsien; Yang, Shieh-Yueh; Horng, Herng-Er; Yang, Che-Chuan; Chieh, Jen-Jie; Chen, Hsin-Hsien; Liu, Bing-Hsien; Chiu, Ming-Jang (Frontiers in Aging Neuroscience, 2018)
Abstract Objective: Parkinson’s disease (PD) has significant clinical overlaps with atypical Parkinsonism syndromes (APS), which have a poorer treatment response and a more aggressive course than PD. We aimed to identify plasma biomarkers to differentiate PD from APS. Methods: Plasma samples (n=204) were obtained from healthy controls and from patients with PD, dementia with Lewy bodies (DLB), multiple system atrophy (MSA), progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), or frontotemporal dementia with (FTD-P) or without parkinsonism. We measured plasma levels of a-synuclein, total tau, p-Tau181, and amyloid beta 42 (Abeta42) by immunomagnetic reduction-based immunoassay. Results: Plasma a-synuclein level was significantly increased in patients with PD and APS when compared with controls and FTD without parkinsonism (p<0.01). Total tau and p-Tau181 were significantly increased in all disease groups compared to controls, especially in patients with FTD (p<0.01). A multivariate and receiver operating characteristic (ROC) curve analysis revealed that a cut-off value for Abeta42 multiplied by p-Tau181 for discriminating patients with FTD from patients with PD and APS was 92.66 (pg/ml)2, with an area under the curve (AUC) of 0.932. An a-synuclein cut-off of 0.1977 pg/ml could separate FTD-P from FTD without parkinsonism (AUC 0.947). In patients with predominant parkinsonism, an a-synuclein cut-off of 1.388 pg/ml differentiated patients with PD from those with APS (AUC 0.87). Conclusions: Our results suggest that integrated plasma biomarkers improve the differential diagnosis of PD from APS (PSP, CBD, DLB and FTD-P).